(untitled) (Quinto Sol, 2013)
This study constitutes the first attempt to approach the identification of the most representative social actors of regional fruit growing –in terms of small exploitation units considered optimal in the early stages of the activity–, their link with other economic agents and their accumulation possibilities of the generated value. We will deal with the stage that includes the start of the activity at the beginning of the 20th century until 1948, when the nationalization of British companies took place. In this regard, the land subdivision process and the consequent appearance of the small owner producer are examined, as well as the productive evolution of the region, to conclude with the qualitative characterization of the operation of the respective subsystem.